Respostas
respondido por:
2
Ola Zilda
A = x - 2
B = 2x + 1
C = x
A² = x² - 4x + 4
A² - B + C = x² - 4x + 4 - 2x - 1 + x = x² - 5x + 3
.
A = x - 2
B = 2x + 1
C = x
A² = x² - 4x + 4
A² - B + C = x² - 4x + 4 - 2x - 1 + x = x² - 5x + 3
.
respondido por:
1
A = x - 2
B = 2x + 1
C = x
P = A.A - B + C
P (x-2).(x-2) - (2x + 1) + x
P = x² - 2x - 2x + 4 - 2x - 1 + x
P = x² - 2x - 2x - 2x + x + 4 - 1
P = x² - 5x + 3
B = 2x + 1
C = x
P = A.A - B + C
P (x-2).(x-2) - (2x + 1) + x
P = x² - 2x - 2x + 4 - 2x - 1 + x
P = x² - 2x - 2x - 2x + x + 4 - 1
P = x² - 5x + 3
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás